2019
DOI: 10.1021/acs.jafc.9b01719
|View full text |Cite
|
Sign up to set email alerts
|

Functional Intronic Variant in the Retinoblastoma 1 Gene Underlies Broiler Chicken Adiposity by Altering Nuclear Factor-kB and SRY-Related HMG Box Protein 2 Binding Sites

Abstract: The present study aimed to search for chicken abdominal fat deposition-related polymorphisms within RB1 and to provide functional evidence for significantly associated genetic variants. Association analyses showed that 11 single nucleotide polymorphisms (SNPs) in intron 17 of RB1, were significantly associated with both abdominal fat weight (P < 0.05) and abdominal fat percentage (P < 0.05). Functional analysis revealed that the A allele of g.32828A>G repressed the transcriptional efficiency of RB1 in vitro, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…These polymorphisms are located in the intron sequence of the IL1R2 gene, but the function remains unknown. Several studies have suggested that intronic SNPs might contribute to the susceptibilities of diseases by affecting the binding of transcription factors and/or RNA splicing to influence gene expression (Cheng et al, 2019; Grimholt et al, 2018). However, the biological function of these SNPs in the IL1R2 gene needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms are located in the intron sequence of the IL1R2 gene, but the function remains unknown. Several studies have suggested that intronic SNPs might contribute to the susceptibilities of diseases by affecting the binding of transcription factors and/or RNA splicing to influence gene expression (Cheng et al, 2019; Grimholt et al, 2018). However, the biological function of these SNPs in the IL1R2 gene needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…These polymorphisms are located in the intron sequence of IL-1R2 gene, but the function is still unknown. Several studies supported that intronic SNPs might contribute to the susceptibilities of diseases by affecting the binding of transcription factor bind and/or RNA splicing to in uence gene expression [27,28]. However, the biological function of these SNPs in the IL1R2 gene needs to further explore.…”
Section: Discussionmentioning
confidence: 99%
“…The β-actin was selected as the reference gene to normalize mRNA expression of target genes. The relative expression of target genes was evaluated using the 2 –ΔΔCT method [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%